2013
DOI: 10.1590/s0074-02762013000100005
|View full text |Cite
|
Sign up to set email alerts
|

Shigella in Brazilian children with acute diarrhoea: prevalence, antimicrobial resistance and virulence genes

Abstract: Diarrhoeal disease is still considered a major cause of morbidity and mortality among children. Among diarrhoeagenic agents, Shigella should be highlighted due to its prevalence and the severity of the associated disease. Here, we assessed Shigella prevalence, drug susceptibility and virulence factors. Faeces from 157 children with diarrhoea who sought treatment at the Children's Hospital João Paulo II, a reference children´s hospital in Belo Horizonte, state of Minas Gerais, Brazil, were cultured and drug sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
4
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 41 publications
7
49
4
10
Order By: Relevance
“…Similarly to our results, Sousa et al (2013) In contrast, also in Brazil, Cruz et al (2014) isolated 30 strains of Shigella spp. from patients with bloody diarrhoea in Manaus between 2007 and 2008, and detected the ipaBCD gene in all strains, and the sen, ial and virF genes were found in 43.3 %, 56.7 % and 43.3 %, respectively, in higher frequencies in comparison with this present study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly to our results, Sousa et al (2013) In contrast, also in Brazil, Cruz et al (2014) isolated 30 strains of Shigella spp. from patients with bloody diarrhoea in Manaus between 2007 and 2008, and detected the ipaBCD gene in all strains, and the sen, ial and virF genes were found in 43.3 %, 56.7 % and 43.3 %, respectively, in higher frequencies in comparison with this present study.…”
Section: Discussionsupporting
confidence: 90%
“…The published literature contains some studies that searched for the presence of virulence genes in strains of S. sonnei isolated in Brazil and any of these studies included strains isolated for a long period of years in that country Sousa et al, 2013;Cruz et al, 2014). In the present study, the presence of important virulence genes found in all strains and other genes related to invasion, and enterotoxin production in some strains, showed the pathogenic potential of strains of S. sonnei isolated over 31 years in an important metropolitan region of São Paulo State.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foodborne infections caused by Shigella and some Salmonella species are responsible for millions of illnesses each year and infants are particularly susceptible to these organisms [5,6]. According to Jain and colleagues [3], shigellosis is still an important public health problem in developing and underdeveloped countries and the ingestion of Shigella dysenteriae in infant formulas can cause potentially devastating consequences to newborns.…”
Section: Dear Editormentioning
confidence: 99%
“…Early use of antibiotics, within the first 72 hours of illness, can limit the clinical course of the disease and the duration of fecal excretion of the pathogen. However, there is a high proportion of Shigella resistant to sulfamethoxazole and trimethoprim, which deserves attention because they are the drugs of choice to treat patients with inflammatory diarrhoea [5,10]. In this study, to evaluate the antimicrobial resistance, the Shigella isolates were submitted to antibiotic susceptibility testing, according to the Clinical and Laboratory Standards Institute guidelines [11].…”
Section: Dear Editormentioning
confidence: 99%